2020
DOI: 10.1101/2020.01.28.923953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expert programmers have fine-tuned cortical representations of source code

Abstract: Expertise enables humans to achieve outstanding performance on domain-specific tasks, and programming is no exception. Many have shown that expert programmers exhibit remarkable differences from novices in behavioral performance, knowledge structure, and selective attention. However, the underlying differences in the brain are still unclear. We here address this issue by associating the cortical representation of source code with individual programming expertise using a data-driven decoding approach. This appr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…Our findings suggest that earlier reports of left-lateralized code-evoked activity ( Siegmund et al, 2014 ) may reflect processing program content rather than code comprehension per se. This distinction should also be considered when interpreting results of other studies of programming effects on brain activity, such as debugging ( Castelhano et al, 2019 ), variable tracking ( Ikutani and Uwano, 2014 ; Nakagawa et al, 2014 ), use of semantic cues or program layout ( Fakhoury et al, 2018 ; Siegmund et al, 2017 ), program generation ( Krueger et al, 2020 ), and programming expertise ( Ikutani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that earlier reports of left-lateralized code-evoked activity ( Siegmund et al, 2014 ) may reflect processing program content rather than code comprehension per se. This distinction should also be considered when interpreting results of other studies of programming effects on brain activity, such as debugging ( Castelhano et al, 2019 ), variable tracking ( Ikutani and Uwano, 2014 ; Nakagawa et al, 2014 ), use of semantic cues or program layout ( Fakhoury et al, 2018 ; Siegmund et al, 2017 ), program generation ( Krueger et al, 2020 ), and programming expertise ( Ikutani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that earlier reports of left-lateralized code-evoked activity (Siegmund et al, 2014) may reflect processing program content rather than code comprehension per se. This distinction should also be considered when interpreting results of other studies of programming effects on brain activity, such as debugging (Castelhano et al, 2019), variable tracking (Ikutani & Uwano, 2014;Nakagawa et al, 2014), use of semantic cues or program layout (Fakhoury et al, 2018;Siegmund et al, 2017), program generation (Krueger et al, 2020), and programming expertise (Ikutani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among these nine contrasts, six contrasts investigated program out-put estimation against control tasks, and two examined BOLD activations during source code inspections. Peak voxel coordinates in Ikutani et al (2020) showed significant correlations between decoding accuracy of source code categories and behavioral performance of program categorization tasks. From the the pro-gramming language perspective, four studies used Java, two used Python, and one study each used C and ScratchJr in the experiments.…”
Section: Resultsmentioning
confidence: 98%
“…We report the thresholded results as an MKDA statistic map with a voxel-level threshold of p ¡ 0.001 (uncorrected) and a cluster threshold of p ¡ 0.05 (family-wise error [FWE]-corrected). Note that our meta-analysis included the peak voxel coordinates reported in Ikutani et al (2020), derived from decoding analysis but not a BOLD contrast, to cover as many available neuroimaging results as possible in the current literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation